Playing Futsall Development Based on Model Variations - Yeni Marlina; Zahara Zahara; Syamsulrizal Syamsulrizal; Muhammad Iqbal (Inspiree)
The  purpose  of  the study. Universitas Syiah Kuala students who attended the Futsal TP course numbered one hundred and fifty people. And researchers determine the sample between forty five to fifty people.